2020
DOI: 10.1108/jfra-08-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Sticky cost behavior and its implication on accounting conservatism: a cross-country study

Abstract: Purpose This paper aims to investigate the impact of cost stickiness on conditional conservatism. Design/methodology/approach The research sample consists of listed companies from 18 countries, using stock market indices of the BRICS, MIST, North Africa, USA and EU over the period ranging from 1997 to 2015. The authors use the firm-fixed effects method in the estimation of the models. Findings The results provide evidence of the existence of cost stickiness and conditional conservatism in the international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 99 publications
(234 reference statements)
0
10
0
3
Order By: Relevance
“…The current research tests the effect of sticky cost behavior on earnings quality, the second and third hypotheses, by establishing the model (2) following Banker and Byzalov (2014), Balakrishnan et al (2014), Bu et al (2015), Banker et al (2016), Silva et al (2019), and Fourati et al (2020). Like Bu et al (2015), the model (2) relies on sales levels rather than changes in sales since the dependent variable is the level of scaled earnings.…”
Section: Model (2) Examining the Impact Of Sticky Cost Behavior On Earnings Qualitymentioning
confidence: 97%
See 3 more Smart Citations
“…The current research tests the effect of sticky cost behavior on earnings quality, the second and third hypotheses, by establishing the model (2) following Banker and Byzalov (2014), Balakrishnan et al (2014), Bu et al (2015), Banker et al (2016), Silva et al (2019), and Fourati et al (2020). Like Bu et al (2015), the model (2) relies on sales levels rather than changes in sales since the dependent variable is the level of scaled earnings.…”
Section: Model (2) Examining the Impact Of Sticky Cost Behavior On Earnings Qualitymentioning
confidence: 97%
“…As a consequence, it is necessary when estimating accounting conservatism to take cost stickiness into account in order to avoid misrepresented estimation. In the same vein, Fourati et al (2020) examined how cost stickiness affects accounting conservatism across 18 countries from 1997 to 2015. The study denoted that ignoring the impact of cost stickiness in the model of Basu (1997) distorts the estimate of accounting conservatism as the study found that accounting conservatism was overvalued by 46.55% when not controlling for cost stickiness.…”
Section: The Implications Of Sticky Cost Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…When management is optimistic about future performance it tends to increase the stickiness cost. Fourati et al (2020) provided notable evidence of the existence of cost stickiness and conditional conservatism in the international context. They conclude that the association between cost stickiness and accounting conservatism changes across country groups and industries.…”
Section: Sticky Cost Literaturementioning
confidence: 99%